Optimization of the Process of Anaerobic Bioconversion of Liquid Organic Wastes - Kovalev, A. (Springer, 2020)
The aim of the work is to study the effect of the multiplicity of substrate supply to the bioreactor on the efficiency and stability of the continuous process of anaerobic bioconversion of organic matter. Due to the fact that organic matter is decomposed by anaerobic microorganisms of different stages sequentially, and when a daily load is applied once a day, the rates of biogas increases significantly at the time of submission, to equalize the rate of biogas output and provide anaerobic microorganisms with substrate of each stage. Maintaining the optimal rate of supply of the daily dose of the substrate in the bioreactor allows to reduce fluctuations in the rate of biogas output during the day; to increase the resistance to organic matter overload; to increase resistance to ammonium nitrogen overloads; to improve the qualitative composition of biogas; to reduce pH fluctuations in the bioreactor. Â© 2020, Springer Nature Switzerland AG.